One Nation Under Drones Legality, Morality, and Utility of Unmanned Combat Systems. - Jackson, John E. (Naval Institute Press, 2018)
One Nation Under Drones is an interesting and informative review of how robotic and unmanned systems are impacting every aspect of American life, from how we fight our wars; to how we play; to how we grow our food. Edited by Professor John Jackson, who holds the E.A. Sperry Chair of Unmanned and Robotic Systems at the United States Naval War College, this highly readable book features chapters from a dozen experts, researchers, and operators of the sophisticated systems that have become ubiquitous across the nation and around the world.